The fluorine link between a supergiant ore deposit and a silicic large igneous province - McPhie, J.; Kamenetsky, V.; Allen, S.; Ehrig, K.; Agangi, Andrea; Bath, A. (2011)
Olympic Dam is a supergiant Fe oxide Cu-U-Au-Ag ore deposit (~9 × 109 t) that is also enriched in rare earth elements (REEs) and fluorine (F). The immediate host to the ore is hydrothermal breccia within granite and volcanic rocks of a Mesoproterozoic silicic large igneous province. Analyses of melt inclusions in quartz phenocrysts in rhyolite show that the silicic magmas of this province were unusually rich in F (up to 1.3 wt%). Fluorite and other F-rich minerals that crystallized from these magmas provided a gigantic reservoir of F. As a result, the Olympic Dam ore-forming fluid was F-rich and had exceptional capacity to transport diverse elements. Further, we infer that hydrofluoric acid, the most corrosive acid known, contributed to hydrothermal breccia formation by dissolution that in turn increased permeability and accelerated the rate of fluid-rock interaction. It is no accident that the world's largest hydrothermal ore deposit occurs in an F-rich silicic large igneous province.